Perencanaan Unit Pengolahan Limbah Cair Tapioka dengan Sistem Up-Flow Anaerbiv Sludge Blanket (UASB) Untuk Industri Skala Menengah - Mukminin, Amirul; Wignyanto, Wignyanto; Hidayat, Nur (Fakultas Teknologi Pertanian Universitas Brawijaya, 2003)
The objectives of this study were to discover the optimum pH treatment combination for the inflow and the optimum holding period for treatment of liquid tapioca waste quality through using anaerobic up-flow anaerobic sludge blanket (UASB) system. This research employed a completely randomized block design with two factors, namely optimum pH levels 5.73 (control) and pH 7 + 1, and the time factor which was divided into 6 periods 2,4,6,8,10, and 12 hours respectively. The data was analyzed through a variance analysis, if there was a discrepancy/an anomaly, then further DMRT tests were initiated, the treatment that produced effluent being within waste quality standards, i.e. with COD of ≤ 300 mg/l, a TSS ≤ of 100 mg/l, a DO of ≤ 6 mg /l and a pH factor of between 6 and 9, it was considered to be the best treatment. However, should there have been more than the treatment with the above results, and then the final choice was based on that treatment which had the lowest UASB start up costs. The results of the tests indicated that pH inflow levels have a most significant effect on COD, DO, and pH effluent levels, but has little effect on TSS. Furthermore, holding periods also have an enormous influence one effluent COD, DO, TSS and pH levels. In addition, the interaction of pH and holding times also have a major effect on effluent TSS levels and a really significant effect on COD, DO and pH. It was found that the DO concentrations from all treatments were less than 6 mg/l. And the treatment that gave a waste discharge into the environment within regulatory standards for COD, TSS, and pH, was the one with a pH input level of 4.73 (control), a holding period of 12 hours and a COD of 283 mg/l, this produced an effluent of 57 mg/l TSS and pH of 7.20. The best treatment was that with a waste inflow of 4.73 pH and holding period of 12 hours, this one also had the lowest start-up costs Rp. 37,875,000 and operational costs Rp. 25,050 per day. The optimum size reactor for small scale industry had a diameter of 3 mm and a height of 5.73 m, and for medium a sized plant, it was of 4 m diameter and 8.88 m in height. For big production plants, the best size was a 10 m, and 18.43 m in height. Keyword: tapioca wastewater, anaerobic up-flow anaerobic sludge blanket (UASB)